Aldol Condensation of Cyclopentanone with Valeraldehyde Over Metal Oxides - Päivi Mäki-Arvela; Nataliya Shcherban; Chloé Lozachmeur; Kari Eränen; Atte Aho; Annika Smeds; Narendra Kumar; Janne Peltonen; Markus Peurla; Vincenzo Russo; Konstantin P. Volcho; Dmitry Yu. Murzin (Springer, 2025)
Kinetics of the cross aldol condensation of valeraldehyde with cyclopentanone was investigated in a batch reactor under atmospheric pressure at 130 °C using heterogeneous metal modified oxides, such as CeO2–MgO, FeO–MgO, FeO–CaO as well as pristine CaO as catalysts. The catalysts were prepared either by evaporation impregnation or deposition precipitation methods and characterized by XRD, TEM, SEM, nitrogen adsorption, ammonia and CO2 TPD. The results revealed that an optimum amount of strong basic sites gives the highest ratio between cross condensation and self-condensation products of valeraldehyde. The highest yield of the desired product 2-pentylidenecyclopentanone (66%) was obtained with FeO–MgO prepared by the deposition precipitation methods.